Pathogenicity of Stagonospora nodorum requires malate synthase - Solomon, P.; Lee, Robert; Wilson, T.; Oliver, Richard (2004)
A gene encoding malate synthase, a key enzyme of the glyoxylate cycle, has been cloned and characterized in the necrotrophic wheat pathogen Stagonospora nodorum. Expression studies of Mls1 showed high levels of transcript in ungerminated spores whereas malate synthase enzyme activities were low. Expression studies in planta found that Mls1 transcript levels decreased ≈ 10-fold upon germination before slowly increasing throughout the remainder of the infection. To characterize Mls1 further, the gene was disrupted in S. nodorum by homologous recombination. In the absence of any supplied carbon source, the mls1 spores were unable to germinate and consequently the mutants were non-pathogenic. Germination and pathogenicity could be restored by the addition of either glucose or sucrose, implying that S. nodorum is reliant upon the catabolism of lipids for infection. Furthermore, analysis of lipid bodies in the mutant strain indicated that lipid mobilization and, consequently, peroxisomal β-oxidation of fatty acids is delayed or inhibited by the disruption of the glyoxylate cycle. This study has demonstrated for the first time in a fungal phytopathogen the requirement of malate synthase for pathogenicity, suggesting that gluconeogenesis is both dependent on the glyoxylate cycle and required for infection.